Identification of polyunsaturated fatty acids as potential biomarkers of osteoarthritis after sodium hyaluronate and mesenchymal stem cell treatment through metabolomics - Yang, Qinyan; Zhao, Yiran; Li, Na; Wu, Jian-Lin; Huang, Xiaolun; Zhang, Mei; Bian, Xiqing; Zhu, Yi-Zhun (Frontiers in Pharmacology, 2023)
Osteoarthritis (OA) is a prevalent joint disorder worldwide. Sodium hyaluronate (SH) and mesenchymal stem cells (MSC) are promising therapeutic strategies for OA. Previous studies showed they could improve knee function and clinical symptoms of OA. However, the mechanism of the therapeutic effects on the improvement of OA has not been clearly explained. In our study, we used a technique called 5-(diisopropylamino)-amylamine (DIAAA) derivatization liquid chromatography coupled with mass spectrometry to find the metabolites in OA synovial fluid under different treatments. After looking into the metabolomics, we discovered that SH and MSC treatment led to the downregulation of ω-6 PUFAs and the upregulation of ω-3 PUFAs. Significantly, the contents of 5(S)-HETE, PGA2, PGB2, and PGJ2 were lower in the MSC group than in the SH group after quantification using DIAAA derivatization-UHPLC-QQQ-MS. This is the first report on the relationship of 11(S)-HETE, PGA2, PGB2, PGF2β, 11β-PGF2α, and DK-PGE2 with OA. Moreover, the correlation analysis of metabolites and inflammation factors showed the positive association of ω-6 PUFAs with proinflammation cytokines, and ω-3 PUFAs with anti-inflammation cytokines. Our results indicated the therapeutic effect of SH and MSC in patients with OA. In addition, this reliable metabolic approach could uncover novel biomarkers to treat OA.